Self-determined motivation in rehabilitating professional rugby union players. Issue 1 (December 2017) - Carson, Fraser; Polman, Remco
Abstract Background The aim of the present study was to explore the views of professional rugby union players during the early rehabilitation, late rehabilitation and return to play stages, following anterior cruciate ligament (ACL) injury. Methods A qualitative dominant, mixed methodological approach was utilized with five players who had suffered an ACL injury requiring reconstructive surgery. A longitudinal approach, concurrent with each player's rehabilitation, consisting of twice monthly interviews, a self-report diary and three established questionnaires (MOS-Social Support Survey, Sherbourne & Stewart, 1991; Sport Climate Questionnaire, Deci & Ryan, n.d.; Injury Rehabilitation Questionnaire, Deci & Ryan, n.d.) were completed. Results Theoretical thematic analysis was conducted on three distinct phases (Early Limited Participation phase, 10 higher order themes; Late Limited Rehabilitation phase, 11 higher order themes; and Return to Play phase, 9 higher order themes) and coded relating to autonomy, competence and relatedness. Conclusions The findings suggest that increased autonomy and control assist emotional and behavioral responses during rehabilitation and return to play, while development of competence increases self-confidence.